PENINGKATAN KOMPETENSI SISWA/I MELALUI PROGRAM KREATIVITAS SEKOLAH SEBAGAI MOTIVASI BELAJAR PESERTA DIDIK SMK NURUL HUDA BAROS SERANG - Ghoni, Ahmad; Nurlelah, Nurlelah (Yayasan Education and Social Center, 2024)
The aim of this Community Service activity is to implement one of the Tri Dharmas of Higher Education. Apart from that, through this Community Service activity, it is hoped that the existence of universities can make a major contribution to the development and application of science in society. The method used in this Community Service is that the implementation team visits Nurul Huda Vocational School, Serang City. Providing training from 28-29 October 2023. This socialization aims to ensure that vocational school students, who are mostly teenagers, understand the importance of competence for themselves, the period of developing their personal potential is very important to prepare graduates ready for work in the future. The method for implementing this PKM is by: 1. Lecture / Presentation Method, 2. Javanese Questioning Method. 3. Sharing Session about developing personal competencies in choosing a career in the future. This sharing session was given to the participants to encourage the participants to take an active role in their environment to increase the development of their personal potential and career planning as well as understand and be able to implement how to manage their own potential optimally as a provision for being able to choose a career early on. The result of this Community Service activity is an increase in the knowledge and skills of participants at Nurul Huda Baros Serang Vocational School, especially in the field of developing personal potential and career planning in the future, namely competence becomes their provision, both now and in the future. It is hoped that the knowledge gained in this Community Service activity will be able to provide enthusiasm in conveying knowledge and provide motivation and contribute to the younger generation, both in the school, campus and community environments. So that PKM is right on target, it is necessary to pay attention to the method of implementing PKM